Radiation research : biomedical, chemical, and physical perspectives : proceedings of the fifth International Congress of Radiation Research held at Seattle, Washington, U.S.A., July 14-20, 1974 - Nygaard, Oddvar F.; Adler, Howard I.; Sinclair, Warren K. (Academic Press, 1975)
Radiation Research: Biomedical, Chemical and Physical Perspectives documents the proceedings of the Fifth International Congress of Radiation Research held in Seattle, Washington, 14-20 July 1974. While the focus of the Congress was on fundamental research, there were several well-attended sessions on the practical aspects of radiation research as it relates to radiotherapy, central station power generation by both nuclear fission and fusion, and the environment. This volume contains 126 papers organized into 31 parts. Beginning with a keynote address and a lecture on the time scale in radiobi.